Highly thermal conductive and electrical insulating polymer composites with boron nitride. (1st March 2020) - Li, Meng; Wang, Mengjie; Hou, Xiao; Zhan, Zhaolin; Wang, Hao; Fu, Hui; Lin, Cheng-Te; Fu, Li; Jiang, Nan; Yu, Jinhong
Abstract: The heat accumulation has become a serious problem due to electronic devices towards high power and intelligence. Highly thermal conductive and electrical insulating polymeric composites are potential to solving the overheating problem of electronic devices. Herein, boron nitride nanosheets (BNNSs) were successfully exfoliated by shear forces generated high pressure. Then, BNNSs and sphere BN (S-BN) were added into the polydimethylsiloxane (PDMS) matrix to prepare composites. The thermal conductivity of the BNNSs/PDMS composites achieved 1.16 W m -1 K -1 at 35 wt% fillers, which is almost 5 times that of pure PDMS and higher than that of S-BN/PDMS composites. The efficient thermal paths were constructed by BNNSs in PDMS matrix leading to enhancing the thermal transport in polymer matrix. Meanwhile, the volume resistances and breakdown strength of BNNSs/PDMS composites reach 7.5 × 10 13 Ω cm and 39.8 V/μm, which are attributed to the superior electrical insulating properties of BNNSs. The result shows that the excellent thermal conductivity and electrical insulation properties of BNNSs/PDMS make it a promising application in the field of thermal management. Graphical abstract: Image 1 Highlights: BNNS filler was a good choice for improving highly thermal conductivity and electrical insulating of PDMS composites..